Shouting from the Ivory Tower: A Marketing Approach to Improve Communication of Academic Research to Entrepreneurs. (March 2014) - Steffens, Paul R.; Weeks, Clinton S.; Davidsson, Per; Isaak, Lauren
Evidence–based practice in entrepreneurship requires effective communication of research findings. We focus on how research synopses can "promote" research to entrepreneurs. Drawing on marketing communications literature, we examine how message characteristics of research synopses affect their appeal. We demonstrate the utility of conjoint analysis in this context and find message length, media richness, and source credibility to have positive influences. We find mixed support for a hypothesized negative influence of jargon, and for our predictions that participants' involvement with academic research moderates these effects. Exploratory analyses reveal latent classes of entrepreneurs with differing preferences, particularly for message length and jargon.